2019
DOI: 10.1115/1.4043665
|View full text |Cite
|
Sign up to set email alerts
|

Nipple Deformation and Peripheral Pressure on the Areola During Breastfeeding

Abstract: Breastfeeding is a complex process where the infant utilizes two forms of pressure during suckling, vacuum and compression. Infant applied compression, or positive oral pressure, to the breast has not been previously studied in vivo. The goal of this study is to use a methodology to capture the positive oral pressure values exerted by infants' maxilla (upper jaw) and mandible (lower jaw) on the breast areola during breastfeeding. In this study, the positive and negative (vacuum) pressure values are obtained si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
1
17
0
2
Order By: Relevance
“…The relative size of the nipple and density of the areola may make it difficult for the infant to take the right depth of breast tissue into his or her oral cavity or may overwhelm the oral cavity, hindering the coordinated movements of the jaw, tongue, and soft palate (Douglas & Geddes, 2018; Geddes & Sakalidis, 2016). In addition, wider nipples and denser areolas may be more difficult for young infants to compress (Alatalo et al, 2019) or may make it more difficult for the infant to latch onto the breast, leading to nipple soreness (Puapornpong et al, 2017). Although these issues would likely resolve as the infant grows and matures, it is quite possible that an inappropriate latch could cause the infant to develop ineffective sucking habits or lead to poor milk transfer and other breastfeeding challenges, resulting in breastfeeding cessation prior to the point when a better match between maternal and infant anatomy is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The relative size of the nipple and density of the areola may make it difficult for the infant to take the right depth of breast tissue into his or her oral cavity or may overwhelm the oral cavity, hindering the coordinated movements of the jaw, tongue, and soft palate (Douglas & Geddes, 2018; Geddes & Sakalidis, 2016). In addition, wider nipples and denser areolas may be more difficult for young infants to compress (Alatalo et al, 2019) or may make it more difficult for the infant to latch onto the breast, leading to nipple soreness (Puapornpong et al, 2017). Although these issues would likely resolve as the infant grows and matures, it is quite possible that an inappropriate latch could cause the infant to develop ineffective sucking habits or lead to poor milk transfer and other breastfeeding challenges, resulting in breastfeeding cessation prior to the point when a better match between maternal and infant anatomy is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1b presents the 5s dynamic pattern of the applied pressures from one of the participate dyads named Infant #3 in a clinical study. 2 Rhythmic and sinusoidal patterns among healthy infant participants were found with an average suckling frequency of approximately 1-2 cycles/s, vacuum range from 12 to 0 kPa, and positive pressures range between 2 and 12 kPa. When the vacuum peaks, oral compression pressure decreases, whereas when the vacuum moves close to atmosphere pressure, oral compression pressure increases.…”
Section: Lactating Breast Model and Infant Applied Pressuresmentioning
confidence: 90%
“…9 While intra-oral pressure can yield adequate volumes of milk for infant consumption, more recent work has demonstrated that mouthing dynamics is also as effective as vacuum at milk removal. 2,3 Related to milk flow measurements, clinical studies can only capture flow velocity at the outlet and measure the total milk consumption for the entire feeding period. Mathematical modeling 13,20 and computational simulations 4,8 have studied the milk flow within the breast using infant oral applied pressures and nipple mouth deformation as boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that assumptions and parameters being used for nonlactating breasts cannot explicitly apply to lactating breasts. [42] To date, US imaging has been the most commonly practiced technique and the initial modality of choice for the evaluation of breastfeeding mechanics. Although safe and relatively inexpensive, US utilization for this purpose requires a sound understanding of both infant and breast anatomy and the ability to implement dynamic scanning techniques unique to this application.…”
Section: Ultrasound Imagingmentioning
confidence: 99%
“…The measurement of intra-oral vacuum or application of biomechanical forces is absent in this technique, and both have a significant role in proper latching and milk extraction. These particular shortcomings are better addressed by [42] Depicting the tongue and the palate via Submental US image [43] Monitoring the movement and position of the tongue during both breast-and bottle-feeding [44] Intra-Oral Vacuum Vacuum measurement of the intra-oral cavity during breastfeeding [45] A breastfeeding diagnostic device to measure sucking microstructure [46] Device with built-in force sensors [47] Multimodal Sensing Synchronization of the endocavity US probe in conjunction with recorded intra-oral vacuum [48] Placement of a US transducer during bottle-feeding together with an intra-oral vacuum measurement using a catheter situated adjacent to the mother's nipple [49] The NTrainer system incorporating a traditional pacifier and a computer-controlled air pump [50] Milk Remove/Intake Monitoring milk removal by weighing the mother [51] A mechanical device for measuring infant sucking behavior [52] Infant test weighing indicating milk consumption [53] Experiment/Simulation Tekscan pressure sensor strip on mothers [54] The breast model of milk extraction during breast-feeding [43,55] Bio-inspired breastfeeding simulator [56] Global Challenges 2021, 5, 2100019 multimodal sensing, which will be discussed in the following sections.…”
Section: Ultrasound Imagingmentioning
confidence: 99%